SPECIATION OF SULFUR IN HUMIC AND FULVIC ACIDS USING X-RAY ABSORPTION NEAR-EDGE STRUCTURE (XANES) SPECTROSCOPY - Morra M.J.; Fendorf S.E.; Brown P.D. (My University, 1997)
Sulfur species in soils and sediments have previously been determined indirectly using destructive techniques. A direct and more accurate method for S speciation would improve our understanding of S biogeochemistry. X-ray absorption near edge structure (XANES) spectroscopy was performed on purified humic and fulvic acids from terrestrial and aquatic environments. This methodology allows direct determination of S species using the relationship that exists with the energy required for core electron transitions and in some cases, correlation with additional spectral features. Soil, peat, and aquatic humic acids were dominated by sulfonates with an oxidation state of +5, but also contained ester-bonded sulfates with an oxidation state of +6. Leonardite humic acid contained ester-bonded sulfate and an unidentified S compound with an oxidation state of +4.0. In contrast, high-valent S in soil, peat, and aquatic fulvic acids was exclusively in the form of sulfonic acids. Reduced S species were also present in both humic and fulvic acids. XANES is a valuable method for the speciation of S in humic materials and of potential use in S speciation of unfractionated soils.